Jornalismo móvel na rotina de trabalho dos repórteres da TV Paraíba - Melo, Cristiane Larissa Fernandes (2020)
The research aims to understand how the incorporation of mobile technologies in the production of newscasts reconfigured journalistic practice in TV newsrooms and also in the work of street and field teams. It starts from the concepts of mobile journalism and journalistic convergence. The investigation focuses on the case study of TV Paraíba about new work routines and different attributions to the daily life of the TV reporter with the insertion of mobile equipment such as smartphones in the routine of these professionals. We seek to understand how the production of news and the routine of reporters were changed from the insertion of the smartphone in the production of content for TV Paraíba news programs, affiliated with Globo network in Campina Grande, in Paraíba. The methodology involves bibliographic research, semi-structured interviews and observation form of the productions. The results show that with the insertion of smartphones in journalistic production, a new, more agile and dynamic production model emerges. A new news format was created, the stand up selfie, which is a stand up recorded by the reporter himself using his mobile phone. And the routine of these professionals has also changed, they now have to deal with a reality where the reporter needs to acquire new skills and accumulate various roles to meet this mobile production model.